Comparative evaluation of intermediate solutions in prevention of brown precipitate formed from sodium hypochlorite and chlorhexidine gluconate. Issue 6 (14th September 2022) - Bueso, Vashti; Parikh, Neha; Terlier, Tanguy; Holland, Julian N.; Sarmast, Nima D.; Jeong, Ji Wook
Abstract: Objectives: To evaluate intermediate treatments between sodium hypochlorite and chlorhexidine gluconate irrigations for the prevention of a toxic brown precipitate in root canal therapy. Materials and Methods: Thirty‐nine premolars were irrigated with 6% sodium hypochlorite and divided into either: No intermediate treatment; Dry paper points; three different irrigations with 17% ethylenediaminetetraacetic acid, deionized water, or 5% sodium thiosulfate. 2% chlorhexidine gluconate was the final irrigant in all groups. Sectioned teeth were analyzed for brown precipitate intensity and area using stereomicroscopy and components related to para‐chloroaniline using Time‐of‐Flight Secondary Ion Mass Spectrometry (ToF‐SIMS). Results: Stereomicroscopy showed that 5% STS significantly reduced brown precipitate intensity and area as compared with no intermediate irrigation ( p  < .05, Chi‐square, generalized linear model, and Tukey's multiple comparison tests). Utilizing ToF‐SIMS, 5% sodium thiosulfate was most effective in reducing the components representing para‐chloroaniline and chlorhexidine gluconate. Conclusion: The 5% sodium thiosulfate was most effective among other intermediate treatments, assessed by stereomicroscopy and ToF‐SIMS.